Frequency of rs731236 (Taql), rs2228570 (Fok1) of Vitamin-D Receptor (VDR) gene in Emirati healthy population - Osman, Enas (Meta Gene, 2015)
Vitamin D is getting more attention everyday due to its importance in maintaining bone and calcium homeostasis, cellular proliferation, differentiation and immune response. Vitamin D is derived from diet or elicited in the skin by the activation of 7-dehydrocholesterol, which is an inert molecule that must be activated by ultraviolet light to form pre-vitamin D3. Recent studies connected the gene encoding for vitamin D (VDR) to the genetic control of bone mass and other diseases. As VDR SNPs have been associated with several disorders and diseases, it's important to investigate the allelic and genotypic distribution among populations. The aim of this study is to determine the frequency of rs731236 (Taq1) and rs2228570 (Fok1) variants in healthy Emirati individuals and compare their genotype and allele distribution with other populations. In this study 282 (female, 187; male, 95) unrelated healthy UAE nationals were involved. Two hundreds and eight two DNA samples been collected to genotype rs731236 (Taq1) and rs2228570 (Fok1) VDR SNPs. Our results indicate that the distribution of the alleles and genotypes of rs731236 (Taq1) and rs2228570 (Fok1) vary considerably in different populations. In the Emirati population the distribution of rs731236 (Taq1) and rs2228570 (Fok1) were AA 38%, AG 42%, GG 20% and AA 27%, AG 42%, GG 31% respectively. The Emirati population genotype and allele distribution of rs731236 (Taq1) and rs2228570 (Fok1) had no difference with Caucasians from USA and France. However, there was significant difference with Asian populations.